Measurement of the forward-backward asymmetry in the B→K*μ(+)μ(-) decay and first observation of the B(s)0→ϕμ(+)μ(-) decay. - Aaltonen, T; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We reconstruct the rare decays B(+)→K(+)μ(+0μ(-0, B90)→K*(892)(0)μ(+)μ(-), and B(s)(0)→ϕ(1020)μ(+)μ(-) in a data sample corresponding to 4.4  fb(-1) collected in pp collisions at √[s]=1.96  TeV by the CDF II detector at the Tevatron Collider. Using 121±16 B(+)→K(+)μ(+)μ(-) and 101±12 B(0)→K(*0)μ(+)μ(-) decays we report the branching ratios. In addition, we report the differential branching ratio and the muon forward-backward asymmetry in the B(+) and B(0) decay modes, and the K(*0) longitudinal polarization fraction in the B(0) decay mode with respect to the squared dimuon mass. These are consistent with the predictions, and most recent determinations from other experiments and of comparable accuracy. We also report the first observation of the B(s)(0)→ϕμ(+)μ(-) decay and measure its branching ratio BR(B(s)(0)→ϕμ(+)μ(-))=[1.44±0.33±0.46]×10(-6) using 27±6 signal events. This is currently the most rare B(s)(0) decay observed.